Management of Locally Advanced and Metastatic Pediatric Nasopharyngeal Carcinoma. Experience of Children Cancer Hospital – Egypt - Hany Abdel Rahman; Wael Zekri; Aml M.El Gaml; Eman Eldebawy; Soha Ahmed; Iman Zaki; Manar Monir; Mohamed Saad Zaghloul (Journal of Otolaryngology Advances, 2015)
Background. Nasopharyngeal carcinoma (NPC) is a rare disease in the pediatric age group; it represents 1% of all pediatrics malignancies, however, it is the predominant malignancy arising in the nasopharynx in this age group. Although NPC is a chemo-radiosensitive disease yet, the optimal dose of radiotherapy and optimal timing of chemotherapy is still not standardized. Methods. This is a retrospective study including all the newly diagnosed pediatric NPC who were diagnosed and treated at the Children Cancer Hospital Egypt (CCHE) during the period from July 2007 to December 2012. All imaging studies (e.g., CT or MRI scans) were reviewed by a senior head and neck radiologist for proper staging and assessment of tumor response. Patients were staged according to AJCC staging system. Modified version of the Response Evaluation Criteria in Solid Tumor (RECIST) was used to assess response. Results. Twenty-six patients were diagnosed and received treatment as NPC in CCHE. Median age was 12 years (range 7.8-17 years). There was a male predominance. Eleven patients (42.3%) were stratified as stage 4, and 11 (42.3%) as stage 3. All patients received 3 cycles of neo-adjuvant chemotherapy followed by concurrent chemo-radiotherapy. IMRT was used to deliver radiotherapy in all patients. The overall response rate (CR and PR) to induction therapy was 73%, 19.3% had SD, while 7.7% had PD. By the end of the study, 18 patients (69.2%) were alive in CR, 5 patients (19.2%) had PD, and 3 patients (10%) lost for follow up. The Mean duration of follow up was 35 months, range 5-66 months. The 3 year OS and EFS and rates were 84.6% and 69.3 % respectively. OS for M0 was 91.3% and for M1 33.3% with statistical significance (p =0.032). Conclusion. Neoadjuvant chemotherapy followed by concurrent chemoradiotherapy using IMRT lead to good clinical end results with limited toxicity. Metastatic disease at presentation was identified as the adverse prognostic factor.
Keywords: Radiotherapy